On the taxonomic status of the varieties of Chorizanthe angustifolia (Polygonaceae) - Gowen, David; Johnson, Leigh A. (Phytotaxa, 2020)
Chorizanthe angustifolia var. eastwoodiae was named by Goodman in 1934, but has since generally been ignored as a taxon. A limited number of C. angustifolia var. angustifolia collections available for comparison and lack of clearly defined characters differentiating the two varieties likely account for the taxonomic concept for C. angustifolia that rejects infraspecific taxa. Nevertheless, several characters previously unnoted in floristic literature distinguish var. angustifolia from var. eastwoodiae. Variety angustifolia is a yellow-green plant with straw-colored tepals that are narrow and long-pointed, and has 3 stamens per flower. Variety eastwoodiae is a pinkish plant with pink, rounded and often erose tepals, with 8–9 stamens per flower. Morphological differences and comparative DNA sequencing indicate the two varieties are better treated as separate species. A new combination (C. eastwoodiae comb. et stat. nov.) is proposed and typification of the name C. angustifolia is clarified. A comparison table of closely related Chorizanthe is provided.